1992
DOI: 10.1016/0300-5712(92)90002-t
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage

Abstract: A critical review of techniques used in the assessment of microleakage in dental restorations is presented. These techniques include the use of air pressure, bacteria, radioisotopes, electrochemistry, chemical tracers and dye penetration. Wide variations in methodologies are revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
139
0
30

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(171 citation statements)
references
References 74 publications
2
139
0
30
Order By: Relevance
“…This is the most commonly used method to assess microleakage of dental materials. 15 It is easy to perform, fast, and economical, but the shortcoming of the technique is the subjectivity of reading the specimens. 16 In our study all specimens were evaluated by the two operators at two times to evaluate measurement error.…”
Section: Discussionmentioning
confidence: 99%
“…This is the most commonly used method to assess microleakage of dental materials. 15 It is easy to perform, fast, and economical, but the shortcoming of the technique is the subjectivity of reading the specimens. 16 In our study all specimens were evaluated by the two operators at two times to evaluate measurement error.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15] The use of silver nitrate in combination with a photo developing solution as a chemical tracer is only distinct from the use of dyes in that the tracers rely on the reaction between both chemicals used. 14,16 Silver stains resist disruption by the coolant when sectioning the tooth, although they are passively deposited. [17][18] In general, the interpretation of silver staining results is subject to controversy.…”
Section: Methodsmentioning
confidence: 99%
“…[32][33][34] Although this study was conducted in vitro, which can be a screening apparatus for ensuing in vivo studies, previous research indicates that data obtained from in vitro microleakage testing may be useful, but not always necessarily reproducible in clinical in vivo settings. [35][36][37] Also, in performing in vitro microleakage investigations, obtaining conclusive information can be problematic, since vast differences in research protocols are reported in the dental literature.…”
mentioning
confidence: 99%